Study of fluidelastic instability in the streamwise and transverse directions through tube array under two-phase flow conditions using pressure effects - Sijiu Qi; Wei Tan; Ke Zhang; Yuancen Wang; Wenjing Lin; Peize Han; Guorui Zhu (Nuclear Engineering and Technology)
The fluidelastic instability (FEI) in heat exchanger tubes has been of widespread concern due to its tendency to cause damage to the tubes. Generally, FEI in the transverse direction of the tube occurs earlier than in the streamwise direction, and the intrinsic frequency of the tube as well as the way of tube distribution have a great influence. The mechanisms involved in inducing FEI need to be further investigated. We set up an air-water two-phase flow water tunnel test system and adopt a normal triangular arrangement plate with a pitch-to-diameter ratio of 1.41 to conduct experiments. It was ensured that FEI could occur in the experimental flow range, by varying the intrinsic frequency of the flexible tube. The fluidelastic instability phenomenon was investigated in a single flexible tube array and a cluster of seven flexible tubes (the central cluster). Comparative analysis was conducted between the results of the two array configurations. The experiments involved concurrent streamwise and transverse directions, and an analysis of the pressure exerted on the flexible tubes. Additionally, the “transitional” state observed in flexible tubes under strongly coupled vibration in the central cluster was explored. The findings indicated that a cluster of seven flexible tubes intensified the vibration coupling between bundles, leading to a more complex flow field around the tube bundle perimeter, consequently exacerbating tube vibration. Furthermore, under the “transitional” state, enhanced stability was manifested. Additionally, instability in the streamwise direction was primarily controlled by the stiffness mechanism; a single flexible tube did not exhibit fluidelastic instability in the streamwise direction, while the central cluster did. This paper recommends an instability constant (K) value of 3.4 for the Connors formula for a normal triangular tube bundle configuration with the pitch-to-diameter ratio of 1.41, thereby providing empirical and theoretical support for the vibration analysis of tube bundles.